The role of a teacher in a CLIL classroom - Papaja, Katarzyna (Glottodidactica, 2013)
CLIL classrooms are not typical language classrooms due to the fact that language is the medium through which content is “transported”. Non-linguistic content is used to teach a language and learners acquire new knowledge but in a foreign language. The following paper provides an outline of research on the role of a teacher in a CLIL classroom. Starting with a brief insight into the phenomenon of CLIL, and a general overview of the qualitative studies based on observations, questionnaires and interviews, the article focuses particularly on the main features of a CLIL teacher.